PENGEMBANGAN KAWASAN GEOPARK KALDERA TOBA DI KABUPATEN SAMOSIR (Development of The Geopark Kaldera Toba Area in Samosir District) - Sahala Fransiskus Marbun; Luthfi Muta’ali; Sudrajat Sudrajat (Universitas Muhammadiyah Gorontalo, 2019)
Abstract - Geopark is an area with boundaries that have been clearly defined and have a large surface area for local economic development. Geopark not only consists of a number of geological diversity that has special interests, scarcity and beauty known as geological heritage, but also cultural diversity and biotic diversity. As one of the districts included in the Toba Caldera Geopark Region, Samosir Regency has a unique location, which is a district where the entire administrative area is the Toba Caldera Geopark Region. This study aims to formulate a strategy to develop Toba Caldera Geopark in Samosir Regency. The method used is descriptive qualitative by using Analysis Hierarchy Process (AHP) analysis techniques. The results showed that the priority strategy for the development of the Toba Caldera Geopark Area in Samosir District was community development, conservation and also economic development. The strategic program that is a priority in the development of the Toba Caldera Geopark Area in Samosir Regency from the aspect of community development is Involving the local community in the preparation of geopark activities programs, Socialization of the concept of geopark to the community, Improvement of geological, biological and cultural education. Keywords: Geopark, Area Development, AHP